Yaşsanmişs önemli yazilim hatalarinin incelenmesi ve kritik öneriler - Kahveci, Ayse; Das, Resul (Institute of Electrical and Electronics Engineers Inc., 2019)
The importance and indispensability of technology in human life is increasing day by day and software systems take place in every area of our lives. The variety of errors and error rate in the software system that we use in many areas of our daily lives provide information about the quality criteria of the software. The minimum error rate in the software modules is one of the many factors that indicate that the software is of good quality. In this paper, the types and types of software errors are examined and the errors that have great risk potential in history are examined. However, taking into account the frequently encountered errors today, critical recommendations have been made for software developers. © 2019 IEEE.
2019 International Conference on Artificial Intelligence and Data Processing Symposium, IDAP 2019 -- 21 September 2019 through 22 September 2019 -- Malatya -- 153040
Keywords: Error types in software; Software engineering; Software faults; Software quality